Pengaruh Pemindahan Ibu Kota Negara terhadap Investasi di Kabupaten Tabalong Kalimantan Selatan - Dyah Sri Wulandari; A. Firsa Ariza; Nurhayati Nurhayati (Journal on Education, 2023)
The purpose of this study is to analyze how much influence the relocation of the State Capital has on Investment in Tabalong Regency, South Kalimantan. This study uses a quantitative method with the type of explanatory research. The sample in this study used a purposive sampling technique. The number of samples in this research is 100 people who have assets or investments from 2019 to 2022 in Tabalong Regency. Then the data is processed using the SmartPLS computer program. The relocation of the National Capital (X) has a significant effect on investment in Tabalong Regency (Y). This study concludes that the relocation of the National Capital from Jakarta to East Kalimantan has also affected investment in other provinces in the vicinity, one of which is Tabalong Regency which is 217 km from the Capital City State, one of the investments that are of great interest to the people in the Tabalong Regency area is Real Assets. Tabalong Regency as a buffer for the National Capital also participates in preparing facilities, infrastructure as the gateway for the Kalimantan region to the National Capital.